A Cross-Cultural Perspective of Supervisory Values: Comment - Robey, Daniel (Academy of Management Journal, 1972)
The article presents comments on the article “A Cross-Cultural Perspective of Supervisory Values,” by Richard B. Peterson in the March 1972 issue. The original article discussed what Peterson calle...